LIFE STYLE OF URBAN SOCIETY (STUDY MEANING FAMILY BOX FAMILY KARAOKE FOR STUDENTS IN HR. SOEBRANTAS STREET PANAM) - Marliza, Ella; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Lifestyle of urban society that often modern actually related with society area as central government bussines, education and entertainment. At first karaoke considered as a expansive entertainment and look as evening entertainment in negative conotation by almost Indonesian people. At the time place of karaoke that first looked negative in as long as reduce because in almost place of karaoke called friendly. Place of karaoke that we done in this research is Family Box the location in HR. Soebrantas Street Panam of Pekanbaru City.The purpose of this research is to find out what the meaning of Family Box karaoke for students and to know what the factors that make students visited Family Box karaoke. The method that used in this research is kualitatif method with descriptive research. In data collections the researcher use a participations observations. observation is equipped with photo cameras. Interview used is indepth interview be guided in interview guide which had been prepared in advance. The device that used in interview is filed note and tape recorder. Data analysis that used in this research is kualitatif data analysis.The results of this research show that karaoke as a lifestyle of urban society. With karaoke students get having fun and satiesfied that you cand relive stress and mind burden that they felt. With hanging out and joking with friends in the room of the karaoke for society is effective to refreshing.Key Words :Karaoke, Students and Meaning.